2005
DOI: 10.1128/iai.73.3.1568-1577.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Live and InactivatedChlamydia trachomatisMouse Pneumonitis Strain Induces the Maturation of Dendritic Cells That Are Phenotypically and Immunologically Distinct

Abstract: The intracellular bacterial pathogen Chlamydia trachomatis is a major cause of sexually transmitted disease worldwide. While protective immunity does appear to develop following natural chlamydial infection in humans, early vaccine trials using heat-killed C. trachomatis resulted in limited and transient protection with possible enhanced disease during follow-up. Thus, immunity following natural infection with live chlamydia may differ from immune responses induced by immunization with inactivated chlamydia. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 56 publications
2
48
0
Order By: Relevance
“…We first analyzed the secretion of IL-12, a proinflammatory cytokine frequently released by DCs and phagocytes in response to pathogens (5,15,16). Interestingly, despite our observations that both Pneumocystis and Saccharomyces ␤-glucan induced costimulatory molecule expression in a manner highly similar to LPS, the production of total IL-12 (IL-12 p70) by DCs after exposure to these fungal cell wall preparations was not stimulated by the fungal isolates ( Fig.…”
Section: Pneumocystis Cell Wall ␤-Glucans Induce Costimulatory Molecumentioning
confidence: 97%
“…We first analyzed the secretion of IL-12, a proinflammatory cytokine frequently released by DCs and phagocytes in response to pathogens (5,15,16). Interestingly, despite our observations that both Pneumocystis and Saccharomyces ␤-glucan induced costimulatory molecule expression in a manner highly similar to LPS, the production of total IL-12 (IL-12 p70) by DCs after exposure to these fungal cell wall preparations was not stimulated by the fungal isolates ( Fig.…”
Section: Pneumocystis Cell Wall ␤-Glucans Induce Costimulatory Molecumentioning
confidence: 97%
“…with Chlamydia (14) or naive mice using MACS CD4 T cell isolation kit (Miltenyi Biotec). CD4 T cells of Ͼ90% purity were obtained as measured by FACS (data not shown).…”
Section: Elisamentioning
confidence: 99%
“…Our previous work has demonstrated that expression of GM-CSF (a cytokine known to mobilize DCs) in the mouse airway significantly enhanced systemic Th1 cellular immune responses following mucosal immunization with inactivated Chlamydia muridarum (13). Subsequent in vitro observations demonstrated that DCs exposed to live or to UV-irradiated C. muridarum develop distinct phenotypes, such that DCs exposed to live Chlamydia become mature and effectively present Ag to Chlamydia-specific CD4 T cells, while DCs exposed to UV-irradiated Chlamydia were less immunologically mature (14). Using GeneChip microarrays we observed that 33 genes were differentially expressed in response to live vs UV-irradiated Chlamydia, including three neutrophil chemoattractant chemokines, KC, MIP-2, and LIX (15).…”
mentioning
confidence: 99%
“…A recent study showed that NK cells can enhance the capacity of DC to present parasitic Ags via the NKG2D receptor pathway (21). The important role of DC in initiation and maintenance of T cell responses to chlamydial infection has been demonstrated by several previous studies using mouse models of C. trachomatis mouse pneumonitis strain, more recently called Chlamydia muridarum (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Su et al (22) reported that i.v.…”
mentioning
confidence: 99%
“…In contrast, by comparing DC from wildtype and IL-10 gene knockout mice, He et al (30) found that IL-10 production by DC was associated with inhibition of Th1 immunity to chlamydial infection. Moreover, Rey-Ladino et al (31) reported that DC with distinct phenotype and cytokine production patterns are different in immunogenicity.…”
mentioning
confidence: 99%